How Cannabis and Alcohol Use Influence Sexual Behavior Among Men Who Have Sex with Men (MSM): A Secondary Data Analysis Using Ecological Momentary Assessment - Bustamante, Maria J; Palfai, Tibor P; Simons, Jeffrey S; Maisto, Stephen A; Beckius, Brooke Z; Kim, Kawon (Journal of studies on alcohol and drugs, 2025)
Heavy drinking is common among men who have sex with men (MSM) and significantly increases HIV acquisition risk. MSM who report heavy drinking also report higher cannabis use, which has also been associated with sexual behaviors known to elevate HIV transmission risk. Despite evidence of associations at the between- subjects' level, the effects of alcohol and cannabis use on sexual risk behavior among MSM who engage in heavy drinking are largely unknown. The current study used ecological momentary assessment (EMA) to examine the between- and within-subject associations of heavy drinking, cannabis use and sexual behavior. This is a secondary data analysis of a study on alcohol intoxication on sexual decision making (Maisto et al., 2021) that included 115 MSM who reported cannabis use and were not using PrEP at the baseline. Participants reported daily alcohol and cannabis use and sexual activities over six weeks. Multilevel multinomial regression was used to evaluate how alcohol and cannabis use were associated with sexual behaviors. Higher alcohol use was associated with higher rates of intercourse at the between-persons level and higher likelihood of all sexual behavior at the event-level. In contrast, cannabis use at the between-person level was associated with an increased rate of CAI relative to both anal intercourse with a condom as well as no sex. At the within-person level, cannabis was associated with increased likelihood of anal sex with or without a condom relative to no sex. Cannabis and alcohol may have independent effects on sexual risk behavior among MSM. Interventions addressing sexual health among MSM who engage in heavy drinking should also consider the additive risks of cannabis use.